Ciudadanía Compleja y Reivindicación Cultural - Mendívil Macías V, José (Acta Universitaria, 2008)
A theoretical characterization of citizenship in a globalized environment is attempted, in order to locate new frames of reference relating to justice, deliberative politics, and cultural vindication, and concludes with an analysis of the ethical conditions of intercultural dialog.
Keywords: Array; Array; Array; Array; Array; Array